1996
DOI: 10.1063/1.116812
|View full text |Cite
|
Sign up to set email alerts
|

Size effects in small oxide confined vertical-cavity surface-emitting lasers

Abstract: Data are presented on small area vertical-cavity surface-emitting lasers with lateral sizes ranging from 5 to 1 μm that use both oxide confinement and a high-contrast distributed Bragg reflector as the upper mirror. Optical loss becomes appreciable for device sizes less than 3 μm in diameter, and is analyzed through measurements of threshold, differential output efficiency, and the far-field radiation patterns. The results suggest that loss of optical confinement occurs for thin apertures and small device size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…3. The increase in threshold current for very small devices is considerably more gradual than what has been recently reported for AlAs/GaAs VCSELs with similar active regions, 16 and indicates that the Al x O y /GaAs DBRs have a decreased optical loss as compared to the AlAs/GaAs system for small optical modes. For example, in another study of VCSELs based on lower AlAs/GaAs DBRs, the threshold nearly doubles from ϳ60 A for a 2 m diameter to ϳ120 A for a 1 m diameter VCSEL.…”
Section: ͓S0003-6951͑97͒00314-8͔mentioning
confidence: 79%
“…3. The increase in threshold current for very small devices is considerably more gradual than what has been recently reported for AlAs/GaAs VCSELs with similar active regions, 16 and indicates that the Al x O y /GaAs DBRs have a decreased optical loss as compared to the AlAs/GaAs system for small optical modes. For example, in another study of VCSELs based on lower AlAs/GaAs DBRs, the threshold nearly doubles from ϳ60 A for a 2 m diameter to ϳ120 A for a 1 m diameter VCSEL.…”
Section: ͓S0003-6951͑97͒00314-8͔mentioning
confidence: 79%
“…This discrepancy of higher power for smaller unoxidized devices may be due to the fact that larger mesa devices require a higher injection current, which, in turn, increases the device temperature. 17 As expected for devices with the same size mesas (23-µm mesa diameter), the oxide confinement device has a lower threshold current as well as a higher light-output power than the unoxidized sample. The slope efficiency is also higher for the oxidized sample.…”
Section: Thermal Modelmentioning
confidence: 83%
“…This shows that for threshold current densities greater than ϳ1 kA/cm 2 , both the threshold current density and slope efficiency are affected by carrier leakage, which greatly exaggerates the influence of lateral optical loss. 6 In fact, even if the optical loss rate of the confined eigenmode saturates for decreasing aperture sizes, 13 gain saturation and carrier leakage can continue to increase the threshold current and decrease the slope efficiency with decreasing aperture size.…”
Section: Microelectronics Research Center Department Of Electrical Amentioning
confidence: 98%
“…For very small active volumes, carrier loss over heterobarriers both increases the threshold and reduces the efficiency. 6,7 Recently we suggested that tunnel injection might aid in increasing the electron confinement for small active areas, and demonstrated an oxide-confined VCSEL based on tunnel injection through a double AlAs barrier. 8 However, tuning between the cavity and QW gain region was not optimum, and the double resonant barrier still showed significant electron leakage at high current density.…”
Section: Microelectronics Research Center Department Of Electrical Amentioning
confidence: 99%
See 1 more Smart Citation